2019
DOI: 10.1111/age.12775
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and genetic diversity of four Henan pig populations

Abstract: SummaryTo investigate the population structure and genetic diversity of Henan indigenous pig breeds, samples from a total of 78 pigs of 11 breeds were collected, including four pig populations from Henan Province, three Western commercial breeds, three Chinese native pig breeds from other provinces and one Asian wild boar. The genotyping datasets were obtained by genotyping‐by‐sequencing technology. We found a high degree of polymorphism and rapid linkage disequilibrium decay in Henan pigs. A neighbor‐joining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Three indigenous pig breeds, the Nanyang Black pig (NY), the Huainan pig (HN), and the Queshan black pig (QS), have been named based on the classification scheme from the National Commission of Animal Genetics resource book (2011). These three pig breeds exhibited strong disease-resistance, high meat yield and early maturation (Qiao et al, 2019). Low density SNP analysis revealed that there has been admixture between Henan indigenous pigs and European commercial pigs (Qiao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three indigenous pig breeds, the Nanyang Black pig (NY), the Huainan pig (HN), and the Queshan black pig (QS), have been named based on the classification scheme from the National Commission of Animal Genetics resource book (2011). These three pig breeds exhibited strong disease-resistance, high meat yield and early maturation (Qiao et al, 2019). Low density SNP analysis revealed that there has been admixture between Henan indigenous pigs and European commercial pigs (Qiao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These three pig breeds exhibited strong disease-resistance, high meat yield and early maturation (Qiao et al, 2019). Low density SNP analysis revealed that there has been admixture between Henan indigenous pigs and European commercial pigs (Qiao et al, 2019). However, the genomic differences and potential role of introgression in Henan indigenous pigs is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The Nanyang black breed of pig is indigenous to the central region of China [ 13 ]. Mineral content, marble stripes, meat color, and IMF content in Nanyang black pigs is significantly higher than those in imported breeds ( P < 0.01) [ 14 16 ]. The Nanyang black pig is, thus, an ideal research model for lipid deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring the genetic characterization of DSE pigs could help for preserving genomic variability, advancing scientific conservation, and contributing to sustainability ( Weitzman, 1993 ). Population genetic data, such as single-nucleotide polymorphism (SNP), are often used to demonstrate population structure and genetic diversity in some other Chinese indigenous pigs, such as Jiangxi native pigs, Henan native pigs, Taihu native pigs, and so on ( Wang et al, 2018 ; Qiao et al, 2019 ; Zhao et al, 2019 ). But limited genetic information–associated literatures were reported about DSE pigs, which reflected that people know little about genetic characteristics of DSE pigs.…”
Section: Introductionmentioning
confidence: 99%